Inorganic geochemistry data from Lake Fazilman, Uzbekistan - Lucas Dugerdil; Guillemette Ménot; Odile Peyron; Dilfuza Egamberdieva; Isabelle Jouffroy-Bapicot; Boris Vannière; Jakhongir Alimov; Elise Luneau; Johanna Lhuillier; Sébastien Joannin (PANGAEA, 2025)
This data table contains the inorganic geochemistry analyses results for a 227 cm-long core core from Lake Fazilman (Fazilman kul, 40.550406 N, 66.589361 E; 1637 m a.s.l.), collected in July 2021 with a 50 cm Russian corer. The data were otbained with a Geotek Multi Sensor Core Logger at the Chronoenvironnement laboratory in Besançon, France. Particularly, data contain the sediment density, the Magnetic Suseptibility (MS, 10.e-5 SI), the optical lightness (L*, %), the ratio 700/400 nm wavelenght and the Relative Absorption-Band Depth between 660 and 670 nm (RADB660-670) calculated following the method of Rein and Sirocko (2002). The sample depth is given in centimeters and the age in year calibrated BP (age-depth model performed with BACON and the IntCal20 calibration curve based on 15 radiocarbon dating; Blaauw et al., 2011; Reimer et al., 2020).
In: Dugerdil, L et al. (2025): Holocene multi-proxy analyses from Lake Fazilman, Uzbekistan: pollen, NPPs, GDGTs, XRF, magnetic susceptibility, climate and vegetation quantitative reconstructions [dataset bundled publication]. PANGAEA, https://doi.pangaea.de/10.1594/PANGAEA.987394 (DOI registration in progress)